Professional male modern boxing: An analysis of activity profile by category - Vicente Puchol; Jose Antonio Sanchez Fuentes; Lluís Albesa Albiol; Toni Caparrós Pons (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study is to examine modern professional male boxing by analyzing world champions differences between winners and losers by categories. 322 male professional boxers (age 28.95 ± 4.10, height 175.26 ± 9.44 cm, and weight 147.82 ± 31.31 lb) were included in this observational descriptive analysis, through 320 fights separated by weight divisions [Heavy (H) (n = 24), Cruiser (C) (n = 48), Light Heavy (LH) (n = 62), Super Middle Weight (SMW) (n = 17), Middle Weight (MW) (n = 68), Light Middle Weight (LMW) (n = 42), Welter Weight (WW) (n = 49), Light Welter Weight (LWW) (n = 28), Light Welter (LW) (n = 33), Super Feather Weight (SFW) (n = 63), Feather Weight (FW) (n = 66), Super Bantam Weight (SBW) (n = 42), Bantam Weight (BW) (n = 30), Super Fly Weight (SFLW) (n = 39), Flyweight (F) (n = 29)]. Differences were found between winners and losers (U = 57804 - 90908.5; p <.001; d = 0.129 - 0.776) for all the variables analyzed. Four significant correlations were highlighted: %PL (Percentage of Punches Landed) (rho = .630); AVG PLxR (Punches Landed Per Round) (rho = .594); AVG PPLxR (Power Punches Landed Per Round) (rho = .517); %PPL (Percentage of Power Punches Landed) (rho = .672) and differences were also observed between weight categories (H = 32.29 - 93.11; p <.001 - .004), except for %PL, AVG JLxR, %JL (Percentage of Jabs Landed) and %PPL. This data suggests that in order to win these events, fighters must deliver precise punches, especially power punches, and that there are differences between the categories with this type of punch (AVG PPLxR).